EDIACARAN FOSSIL PRESERVATION: TAPHONOMY AND DIAGENESIS OF A DISCOID BIOTA FROM THE AMADEUS BASIN, CENTRAL AUSTRALIA - Mapstone N.B.; McIlroy D. (My University, 2006)
Aspects of the preservation of the enigmatic soft-bodied Ediacara biota in relatively coarse-grained siliciclastic sediments remain unresolved. The taphonomic model proposed by Gehling in 1999 is here validated through examination of previously unpublished discoid fossils from the shallow marine-deltaic Arumbera Sandstone in the Amadeus Basin. Within the Flinders-style preservation, the model predicts stalked-frondose organisms attached by a discoid-holdfast to a microbial mat encrusted sea-bed, with sedimentation as periodic storm-event beds during a terminal Neoproterozoic taphonomic window. A pyrite sole-veneer provided critical fossil rigidity during burial. The sequence of sedimentation events presented here advances a slightly modified Gehling model. No direct evidence of pyrite is detected; instead, a thin haematite/clay coating covers fossil hyporelief surfaces. Nevertheless, an original pyrite sole-veneer is indirectly validated by tracing its diagenetic history through to today's haematite. Detailed petrography demonstrates reducing conditions during eodiagenesis that remained anoxic mildly alkaline through mesodiagenesis, thus the pyrite sole-veneer survived deepest burial. Meteoric water penetrated the deep regolith during prolonged telodiagenesis creating oxic mildly acidic pore-water, so pyrite oxidised and hydrolised to haematite. The applicability of Gehling's model is higher where marine shelf sediments subsided continuously. In shallower or eroded areas that experienced intermittent meteoric eodiagenesis, diagenetic history was different and Ediacaran fossil preservation unlikely. Diagenetic history, therefore, has crucial implications for Ediacaran fossil preservation. © 2006 Elsevier B.V. All rights reserved.
Keywords: AMADEUS BASIN; DIAGENESIS; DISCOID FOSSILS; EDIACARAN; SOLE-VENEER; TAPHONOMY; Precambrian::Proterozoic::Neoproterozoic::Ediacaran; Докембрий::Протерозой::Неопротерозойская::Эдиакарий